2018
DOI: 10.1021/acs.cgd.8b01360
|View full text |Cite
|
Sign up to set email alerts
|

Hydrates and Solvates of Acotiamide Hydrochloride: Crystallization, Structure, Stability, and Solubility

Abstract: This paper elucidated eight crystal structures of acotiamide hydrochloride (AH) via single-crystal X-ray diffraction (SCXRD) with water (1AH-1W-I, 1AH-3W), methanol (1AH-1M), methanol and water (1AH-1W-1M-I, 1AH-1W-1M-II), ethanol (1AH-1E), ethanol and water (1AH-1W-1E), and n-propanol (1AH-1P). Two influencing factors, water content and solvent type, were investigated for their effects on the formation of distinct hydrates and solvates. In addition, the stability and solubility of these solid phase forms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 46 publications
2
18
1
Order By: Relevance
“…The overlap diagrams of the acotiamide cations (Figs. S1a and S1b in the supporting information) show that all N4 atoms bound to the isopropyl group are protonated, and research papers SÁ Á ÁO4 intramolecular interactions are observed in the five AH solvates, consistent with the eight previously reported crystals (Zhang et al, 2019).…”
Section: Single-crystal X-ray Diffraction Structure Analysissupporting
confidence: 86%
See 4 more Smart Citations
“…The overlap diagrams of the acotiamide cations (Figs. S1a and S1b in the supporting information) show that all N4 atoms bound to the isopropyl group are protonated, and research papers SÁ Á ÁO4 intramolecular interactions are observed in the five AH solvates, consistent with the eight previously reported crystals (Zhang et al, 2019).…”
Section: Single-crystal X-ray Diffraction Structure Analysissupporting
confidence: 86%
“…Similar to the eight previously reported crystals (Zhang et al, 2019), the intramolecular hydrogen bonds in 1AH-1W-1DMF and 1AH-1W-1DMSO generated six-membered ringlike structures (Fig. S1a) via the interactions between the O1H group and the C O4 group.…”
Section: Single-crystal X-ray Diffraction Structure Analysissupporting
confidence: 85%
See 3 more Smart Citations